Supplementary Lateral Extra-articular Tenodesis for Residual Anterolateral Rotatory Instability in Patients Undergoing Single-Bundle Anterior Cruciate Ligament Reconstruction: A Meta-analysis of Randomized Controlled Trials. Issue 5 (4th May 2021) - Mao, Yunhe; Zhang, Kaibo; Li, Jian; Fu, Weili
Background: The combination of lateral extra-articular tenodesis (LET) with primary single-bundle anterior cruciate ligament (ACL) reconstruction (ACLR) remains controversial. Purpose: To determine whether the combination of LET with single-bundle ACLR provides greater control of anterolateral rotatory instability and improved clinical outcomes compared with ACLR alone. Study Design: Systematic review; Level of evidence, 2. Methods: PubMed, Embase, and the Cochrane Central Register of Controlled Trials databases were searched between inception and July 1, 2020. Level 1 or 2 randomized controlled trials that compared isolated single-bundle ACLR with combined LET with ACLR were included. Data were meta-analyzed for the primary outcome measure of knee stability and the secondary outcome measures of patient-reported outcome scores, return to sports, and graft failure. Dichotomous variables were presented as relative risks (RRs), and continuous variables were presented as mean differences (MDs) and standardized MDs (SMDs). Results: A total of 6 studies involving 1010 patients were included. Pooled data showed that the ACLR+LET group had a lower incidence of the pivot shift (RR, 0.56 [95% CI, 0.45 to 0.69]; P < .00001), a higher postoperative activity level (MD, 0.47 [95% CI, 0.15 to 0.78]; P = .004), and a lower risk of graft failure (RR, 0.35 [95% CI, 0.21 to 0.59]; P < .00001) than did the ACLR group. However, there were no statistically significant differences in primary outcomes including positive Lachman test findings (RR, 0.76 [95% CI, 0.48 to 1.21]; P = .26) or side-to-side differences (SMD,  –0.43 [95% CI,  –0.95 to 0.09]; P = .11) or in secondary outcomes including International Knee Documentation Committee scores (SMD, 0.25 [95% CI,  –0.06 to 0.56]; P = .11) or Lysholm scores (SMD, 0.28 [95% CI,  –0.06 to 0.62]; P = .11). Although the overall rate of return to sports was not significantly different between the groups (RR, 0.97 [95% CI, 0.90 to 1.03]; P = .33), the activity level was higher in the ACLR+LET group. Conclusion: The addition of LET to primary single-bundle ACLR produced greater knee stability, a higher activity level, and a lower incidence of graft failure than did ACLR alone. There may be a role for adding LET to ACLR for the treatment of ACL injuries.